Effects of Online Teaching and Learning on Learning Outcomes according to TQF in Nursing Students - Chaiwongnakkapun, Chulawaree (Journal of Nurses Association of Thailand Northern Office, 2021)
This one-group quasi-experimental research aimed to investigate the effects of online teaching and learning on Learning outcomes according to Thai Qualifications Framework (TQF)in Nursing Students. The samples were 148 nurse students of Boromarajonani College of Nursing Phrae, in an academic year 2019; also 5 nurse instructors who provided online learning for those students. The instruments were: 1) an online learning handbook with a content validity index (CVI) of 0.85; 2) a record of hours in each subject in the nursing science curriculum (New Curriculum of 2015), hours of online instruction/learning and instruction methods for the second term of the 2019 academic year with an index of consistency of 1.00; 3) an evaluation form for evaluating learning achievements according to the Thai Qualifications Framework (TQF) with an index of consistency of 0.98 and a reliability score of 0.99; 4) a questionnaire on satisfaction toward online learning with an index consistency of 0.98 and a reliability score of 0.99; and 5) interview questions which had an index of consistency of 0.96. The findings revealed that nursing students in every year of study had high learning achievements according to the Thai Qualifications Framework. The mean scores of learning achievements in students Year I, II, and III according to TQF were 4.23 (S.D. = 0.57), 4.06 (S.D. = 0.59), and 3.98 (S.D. =0.58), respectively. The mean scores of students’ year I, II, and III. The learning satisfaction of students’ year I, II, and III were 4.01 (S.D. = 0.49), 4.10 (S.D.= 0.59) and 3.97 (S.D. = 0.64), respectively. The results of qualitative analysis of the interview scripts were found tohave learning achievements consistent with the TQF in each subject. Noticeably, students had the highest leaning achievement in morals and ethics. Students made behavioral changes to be enthusiastic and were responsible when studying and delivered assignments on schedule. Also, students had to pay more attention and put more efforts to study. Students had to manage personal time and be honest by not copying the work of others. Nurse instructors were able to design online learningactivities, supporting students to achieve learning standards consistent with the TQF in all five areas. Online learning was not a limitation for creating learning achievements and students of every year had high overall satisfaction with online learning. Students had the highest satisfaction with clear explanations for TQF 3-4 and objectives of each subject. Students had the least satisfaction with the suitability of online classroom environments.